MicroRNA regulation by the DNA and RNA binding proteins EWS and FUS - Fernandes, Ana Miguel Guterres Coelho, 1988- (2013)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2012